2021
DOI: 10.3390/nu13020550
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition, Digestion, and Absorption Differences among Neonatal Feeding Strategies: Potential Implications for Intestinal Inflammation in Preterm Infants

Abstract: Necrotizing enterocolitis (NEC) is a significant cause of morbidity and mortality in the neonatal population. Formula feeding is among the many risk factors for developing the condition, a practice often required in the cohort most often afflicted with NEC, preterm infants. While the virtues of many bioactive components of breast milk have been extolled, the ability to digest and assimilate the nutritional components of breast milk is often overlooked. The structure of formula differs from that of breast milk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 199 publications
(262 reference statements)
0
3
0
Order By: Relevance
“…Although the authors found no differences in microbial diversity or community structure, contrary to our findings, they did show a ). Although speculative, higher fat intakes combined with a lack of bile saltstimulated lipase from pasteurizing HMBF may contribute to fat malabsorption, lipid oxidation, and reactive oxygen species formation, especially with lower antioxidant intakes (Burge et al, 2021;O'Connor et al, 2015). Among VLBW infants, oxidative stress and redox imbalances have previously been correlated with higher Enterobacteriaceae abundance (Cai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors found no differences in microbial diversity or community structure, contrary to our findings, they did show a ). Although speculative, higher fat intakes combined with a lack of bile saltstimulated lipase from pasteurizing HMBF may contribute to fat malabsorption, lipid oxidation, and reactive oxygen species formation, especially with lower antioxidant intakes (Burge et al, 2021;O'Connor et al, 2015). Among VLBW infants, oxidative stress and redox imbalances have previously been correlated with higher Enterobacteriaceae abundance (Cai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…1 Small vs large MFGs may be differentially affected by digestion due to variations in lipid profiles. 59 In bovine milk, smaller MFGs contain less long-chain but more medium-chain FAs and myristic acid in the core. 47 Gastric lipases preferentially hydrolyze short-and medium-chain FAs, and so the size of fat globules will affect the digestion rate and release of these FAs.…”
Section: Impact Of Processing Of Milkmentioning
confidence: 99%
“…71 Lipid digestion and absorption are also affected by dietary fat composition. 72 Fatty acids with shorter chain length and higher degrees of unsaturation are absorbed more efficiently without the need for lipase or bile salts. 73 Therefore, commercial formulas are often designed to contain fats with more MCTs.…”
Section: Digestion Of Hm-borne Saturated Fatsmentioning
confidence: 99%